Genetic diversity of human isolates of salmonella enterica serovar enteritidis in malaysia - Bakeri, S.A.; Yasin, R.M.; Koh, Y.T.; Puthucheary, S.D.; Thong, Kwai Lin (Wiley, 2003)
Aims: The study was undertaken to determine clonal relationship and genetic diversity of the human strains of Salmonella enterica serovar Enteritidis isolated from 1995 to 2002 from different parts of Malaysia. Methods and Results: Antimicrobial susceptibility test, plasmid profiling and pulsed-field gel electrophoresis were applied to analyse 65 human isolates of S. Enteritidis obtained over an eight year period from different parts of Malaysia. Four nonhuman isolates were included for comparison. A total of 14 distinct XbaI - pulsed- field profiles (PFPs) were observed, although a single PFP X1 was predominant and this particular clone was found to be endemic in Malaysia. The incidence of drug resistant S. Enteritidis remained relatively low with only 37 of the strains analysed being resistant to one or more antimicrobial agents. All except one resistant strain carried at least one plasmid ranging in size from 3.7 to 62 MDa giving nine plasmid profiles. The three isolates from raw milk and one from well-water had similar PFPs to that of the human isolates. Conclusions: Salmonella Enteritidis strains were more diverse than was previously thought. Fourteen subtypes were noted although one predominant clone persisted in Malaysia. The combination of pulsed- field gel electrophoresis, plasmid profiling and antibiograms provided additional discrimination to the highly clonal strains of S. Enteritidis. Significance and Impact of the Study: This is the first report to assess the genotypes of the predominant clinical S. Enteritidis in different parts of the country. As S. Enteritidis is highly endemic in Malaysia, the data generated would be useful for tracing the source during outbreaks of gastroenteritis in the study area.